2014
DOI: 10.4103/2225-4110.126632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Complementary and Alternative Medicine Therapy and Conventional Therapy Use for Musculoskeletal Disorders Management and Its Association with Job Satisfaction among Dentists of West India

Abstract: Musculoskeletal problems have become a significant issue in the profession of dentistry. There are currently no recommended effective disease-preventing and modifying remedies. High prevalence rates for musculoskeletal disorders (MSDs) among dentists have been reported in the literature. Complementary and alternative medicine can be helpful in managing and preventing the MSDs. The purpose of this study was to determine if dentists in the western part of India are using complementary and alternative medicine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…22 The prevalence of MSDs among dentist differs from region to region. A study from Uttar Pradesh 8 reported that 82%, 90% (Uttrakhand), 23 and 79% (west India) 24 of dentists suffer from MSD, whereas this study reports that 71% of dentists suffer from MSD. The difference may be due to the level of ergonomic awareness or use of preventive measures.…”
Section: Discussioncontrasting
confidence: 67%
“…22 The prevalence of MSDs among dentist differs from region to region. A study from Uttar Pradesh 8 reported that 82%, 90% (Uttrakhand), 23 and 79% (west India) 24 of dentists suffer from MSD, whereas this study reports that 71% of dentists suffer from MSD. The difference may be due to the level of ergonomic awareness or use of preventive measures.…”
Section: Discussioncontrasting
confidence: 67%
“…According to the present study result out of 86 (100.0%) dental surgeons the overall mean age was 35.7 (±5.7) years with range 28-62 years, 61.6% were male, 88.4% were married, 91.9% were Muslim, the overall mean BMI was 24.05 (±3.238) with range 17.61 -33.13. Regarding job related characteristics it was found that the mean professional experience, the mean practicing hours per week were 12.6 (±5.1) years, with range 6 -32 years, 46.5 (±13.5) hours, with range 21-96 hours respectively and average number of patients attended per day was 10 (±4.9) with range 3 -30 patients, which was close to the study findings by Batham et al [8] The current study result shows that 63.9%, 47.3% of the participants reported pain and discomfort in at least one body region in the last 12 months and the last 7 days respectively, quite higher prevalence observed in at least one body region in the past 12 months in different studies like 79% (n=2166) in Gupta et al [9] , 83.1% (n=213) in Saxena et al [10] , 86.8% in KiHun et al [11] , 92% in Batham et al [8] . In comparison to present study much higher prevalence of MSDs among the dental practitioners in past 12 months observed in different countries study like America (76.0%) [12] , India (78.0%) [13] , Australia (87.2%) [14] , Poland (92.0% ) [15] , Brazil (65.6%) [16] , Saudi Arabia (77.9%) [17] and in Bangladesh a study by Jahan et al [18] found that 90.0% dental practitioners were suffering from musculoskeletal pain during work in last 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, herb-based formulations are likely to replace Chlorhexidine as soon as intense antimicrobial, palatable, and cost-effective preventive strategies are available. Demand for alternative medicine is on increase (22, 23, 24). However, future studies (with a long-term rinsing period) can be done to extrapolate the advantages and disadvantages of this herbal product.…”
Section: Discussionmentioning
confidence: 99%